Reoperation for calcified aortic homograft after aortic root replacement. (6th November 2015) - Gyoten, Takayuki; Hirota, Masanori; Yoshida, Minoru; Kondo, Taichi; Hoshino, Joji; Isomura, Tadashi
Background: We report three cases undergoing reoperation with previous aortic homograft implantation due to structural valve deterioration. Case: For two cases with severe calcified aortic wall of the homograft and dehiscence of the aortic root, aortic root replacement was indicated. For the last case with less calcified aortic wall, aortic valve replacement was indicated via the aortotomy on the homograft, which required patch plasty for the defect of the stiff aortic wall. Conclusion: The distribution and extent of calcification of the aortic homograft would be the most important factor to determine operative procedures, contributing to successful outcomes.